Chaperone-Mediated Autophagy Upregulation Rescues Megalin Expression and Localization in Cystinotic Proximal Tubule Cells - Zhang, Jinzhong; He, Jing; Johnson, Jennifer L.; Rahman, Farhana; Gavathiotis, Evripidis; Cuervo, Ana Maria; Catz, Sergio D. (Frontiers in Endocrinology, 2019)
Cystinosis is a lysosomal storage disorder caused by defects in CTNS, the gene that codes for the lysosomal cystine transporter cystinosin. Patients with nephropathic cystinosis are characterized by endocrine defects, defective proximal tubule cell (PTC) function, the development of Fanconi syndrome and, eventually, end-stage renal disease. Kidney disease is developed despite the use of cysteamine, a drug that decreases lysosomal cystine overload but fails to correct overload-independent defects. Chaperone-mediated autophagy (CMA), a selective form of autophagy, is defective in cystinotic mouse fibroblasts, and treatment with cysteamine is unable to correct CMA defects in vivo, but whether the vesicular trafficking mechanisms that lead to defective CMA in cystinosis are manifested in human PTCs is not currently known and whether PTC-specific mechanism are corrected upon CMA upregulation remains to be elucidated. Here, using CRISPR-Cas9 technology, we develop a new human PTC line with defective cystinosin expression (CTNS-KO PTCs). We show that the expression and localization of the CMA receptor, LAMP2A, is defective in CTNS-KO PTCs. The expression of the lipidated form of LC3B, marker of other form of autophagy, macroautophagy, is decreased in CTNS-KO PTCs indicating decreased autophagosome number under basal conditions; however, the autophagic flux is functional, as measured by induction by starvation or by blockage using the v-ATPase inhibitor bafilomycin A, and by degradation of the macroautophagy substrate SQSTM1 under starvation and proteasome inhibited conditions. Previous studies showed that LAMP2A accumulates in Rab11-positive vesicles in cystinotic cells. Here, we show defective Rab11 expression, localization and trafficking in CTNS-KO PTCs as determined by confocal microscopy, immunoblotting and TIRFM. We also show that both Rab11 expression and trafficking in cystinotic PTCs are rescued by the upregulation of CMA using small-molecule CMA activators. Cystinotic PTCs are characterized by PTC de-differentiation accompanied by loss of the endocytic receptor megalin, and megalin recycling is regulated by Rab11. Here we show that megalin plasma membrane localization is defective in CTNS-KO PTCs and that its expression is rescued by treatment with CMA activators. Altogether, our data support that CMA upregulation has the potential to improve PTC function in cystinosis.